Analisis Perkembangan Koperasi Mahasiswa Universitas Negeri Padang - Putri, Afika; Irianto, Agus (Universitas Negeri Padang, 2024)
This research aims to determine the causes of the decline of KOPMA UNP and the factors that influence its development. This research uses a descriptive qualitative approach. Data collection methods include observation, interviews, and documentation. This research involved 12 informants. Data analysis includes reduction, presentation and drawing conclusions as well as using triangulation to validate the data. Results of the study were obtained. 1) The covid-19 epidemic caused a drop in KOPMA UNP development by requiring all business activities to be conducted online, so that the business was not optimally run, which had an impact on the decrease in SHU obtained, namely in 2019 as much as Rp. 50,088,012, decreased in 2020 to Rp. 3,108,204, continued to decrease in 2021 Rp. (2,129,098), decreased again in 2022 Rp. (-6,875,999). In 2023, KOPMA's SHU has increased even though it still has a loss of IDR (-926,907). 2) Factors that affect the development of KOPMA UNP include the covid-19 pandemic, less strategic business locations, lack of business promotion and low professional and responsible human resources.